Press gang - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
There ll be some changes soon in the quality of articles in several West African newspapers and radio programmes. At the end of May 2002, in Bouaké, Côte d Ivoire, 19 journalists from seven francophone countries followed a course on packaging...